ARCHITECTURE OF INFORMATION SYSTEM OF DIAGNOSTICS OF TECHNICAL CONDITION OF BUILDING FOUNDATIONS - Терентьєв, Олександр; Горбатюк, Євгеній; Тисленко, Олександр; Зубрій, Іван; Макарчук, Олександр (SWorldJournal, 2024)
This work highlights issues related to the reliability of building foundations. The reliability of the foundation of buildings is its ability to perceive external influences and transfer them to the basis when ensuring the normal operation of structures.